Af’al Rasul dan Implikasinya Terhadap Hukum Fikih - Mustaqim, Rizki (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2019)
Majority of muslims believed that all the speech and deeds of prophet Muhammad (Peace be upon him) is a revelation. Because Muhammad occupies the position as an apostle who serves as a transmitter of Islamic teaching. Then indirectly, none of the words or deeds are done without the identity of revelation and supervision of Allah. However, it doesn’t mean that Muhammad is separated from Humanity side as human being. Muhammad remained as an ordinary human who also possessed life and spiritual needs as human being. But there are some muslims who have not fully understood about the action of Muhammad, not a few who still assume that any actions done by Muhammad contain legal consequences that binded or otherwise. From that perspective there needs to be an deeper review of the activities of Muhammad deeds. Such in reviews have been conducted by Ushuliyyun, ultimately found among some of Muhammads action born of his spontaneity, initiative or humanitarian attitude and as well as acts that are peculiar to him alone. In the end, it will have implications on different contens and levels of laws. From what indicates to the compulsory law, sunnah, or just to show permissibility only.